Concentration-compactness type principle for systems with critical terms in RN - Bonaldo, L. M.M.; Hurtado, E. J. [UNESP]; Neves, W. (Elsevier, 2024)
In this paper, we obtain some important variants of the Lions and Chabrowski Concentration-compactness principle, for nonlinear systems in the context of fractional Sobolev spaces with variable exponents. As an application of the results, we show the existence and asymptotic behaviour of nontrivial solutions for elliptic systems involving a new class of general nonlocal integrodifferential operators with variable exponents and critical growth conditions in RN.
Keywords: Critical nonlinearities; Fractional Sobolev space with variable exponents; Fractional systems; Nonlocal integrodifferential operator; Variational methods